2008
DOI: 10.1007/s00436-008-0985-5
|View full text |Cite
|
Sign up to set email alerts
|

Fas/FasL-dependent apoptosis of hepatocytes induced in rat and patients with Clonorchis sinensis infection

Abstract: To investigate the injury and pathogenesis of Clonorchis sinensis (C. sinensis) to hepatocytes, the liver samples from Wistar rats and patients with C. sinensis infection were examined. The typical histopathological findings of clonorchiasis were observed in rats 4 to 12 weeks postinfection, and majority hepatocytes exhibited hydropic degeneration, even some hepatocytes showed densely condensed nuclei suggesting apoptosis in liver tissue. Apoptosis was found around the central vein or portal areas of liver tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…sinensis infection is regarded as an important cause of hepatic fibrosis (Rana et al 2007), which was first associated with liver flukes over 30 years ago (Ch'In et al 1955). Several reports have indicated that the ESP of C. sinensis may play key pathogenic roles in the development of hepatic and bile duct diseases Kim et al 2008Kim et al , 2009aZhang et al 2008). However, the components of the C. sinensis ESP (Li et al 2004;Hu et al 2009a) and their molecular mechanism of pathogenicity remain obscure.…”
Section: Discussionmentioning
confidence: 99%
“…sinensis infection is regarded as an important cause of hepatic fibrosis (Rana et al 2007), which was first associated with liver flukes over 30 years ago (Ch'In et al 1955). Several reports have indicated that the ESP of C. sinensis may play key pathogenic roles in the development of hepatic and bile duct diseases Kim et al 2008Kim et al , 2009aZhang et al 2008). However, the components of the C. sinensis ESP (Li et al 2004;Hu et al 2009a) and their molecular mechanism of pathogenicity remain obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Cell death involving TUNEL-positive hepatocytes was found in tissue around the central vein or portal areas or rats infected with high parasite loads [46]. Whether this cell death was induced by factors released by the parasite or by inflammatory cells is unknown.…”
Section: When Should Cell Death Be Called Apoptosis?mentioning
confidence: 99%
“…The adult worms inhabit the intrahepatic bile duct and cause clonorchiasis, which is characterized by hyperplasia and metaplasia in the intrahepatic bile duct epithelium [2]. Persistent and chronic infection often lead to hepatobiliary diseases, including cholangitis, cholelithiasis, cholecystitis, pancreatitis, hepatic fibrosis, cholangiocarcinoma and liver cancer [3], [4], [5]. C. sinensis has been classified by the International Agency for Research on Cancer (IARC) as a group 1 biocarcinogen to humans [6].…”
Section: Introductionmentioning
confidence: 99%